Ideas from Complex Systems Theory: Peer-led Community Preventive Health for a WHO (2007) ‘Whole Prison’ Approach to Health - Graham Betts-Symonds (Journal of Family Medicine and Preventive Medicine, 2026)
This article is presented following fourteen years of experience with an innovative approach to preventive health in all Irish Prisons. During this period, University-led and internal evaluations have demonstrated increased engagement with prison populations by trained inmate peer educators, linked to formal prison health, psychology and addiction service professionals [1-3].